2014
DOI: 10.1002/jcp.24677
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Responses in Vascular Smooth Muscle Cells Involve cGMP‐Dependent Protein Kinase (PKG)

Abstract: Published data provide strong evidence that heparin treatment of proliferating vascular smooth muscle cells results in decreased signaling through the ERK pathway and decreases in cell proliferation. In addition, these changes have been shown to be mimicked by antibodies that block heparin binding to the cell surface. Here we provide evidence that the activity of protein kinase G is required for these heparin effects. Specifically, a chemical inhibitor of protein kinase G, Rp-8-pCPT-cGMS, eliminates heparin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 49 publications
(87 reference statements)
5
33
0
Order By: Relevance
“…The heparin effects in ECs are mimicked by HRmAbs that bind to a heparin receptor. The observations that pretreatment with antibodies to a putative heparin receptor decreases TNF␣-induced JNK and p38 activation and decreases stress fiber formation are consistent with previous reports showing that these antibodies mimic the effects of heparin in VSMCs (19,22,24). Here we provide functional evidence that the anti-inflammatory effects of heparin in ECs are mediated through the heparin receptor TMEM184A, as seen in VSMCs (28).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The heparin effects in ECs are mimicked by HRmAbs that bind to a heparin receptor. The observations that pretreatment with antibodies to a putative heparin receptor decreases TNF␣-induced JNK and p38 activation and decreases stress fiber formation are consistent with previous reports showing that these antibodies mimic the effects of heparin in VSMCs (19,22,24). Here we provide functional evidence that the anti-inflammatory effects of heparin in ECs are mediated through the heparin receptor TMEM184A, as seen in VSMCs (28).…”
Section: Discussionsupporting
confidence: 92%
“…This causes ECs to become vasoconstrictive and, eventually, dysfunctional (38,57). Recent studies have shown that the effects of heparin in VSMCs involve cGMP-dependent protein kinase (22). We hypothesize that the effects of heparin in ECs might also be dependent on cGMP-dependent protein kinase and that the heparin-induced increased cGMP prior to exposure to TNF␣ could prevent the effects resulting from changes in NO production.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations